Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Berbelanja Pada Toko Modern Di Yogyakarta - Pril Ranto, Dwi Wahyu (Jurnal Bisnis Teori & Implementasi)
This study aims to examine the impact of service quality dimensions consisting of tangibles, reliability, responsiveness, assurance and empathy towards customer satisfaction on modern stores in Yogyakarta. The population in this study are the customers who purchases on modern stores in Yogyakarta. While the samples taken are customers who purchases at Indomaret, Alfamart and Pamella. Sample in this study amounted 100 people.This study used a convenience sampling technique that is because of the ease of sampling and purposive sampling, criteria have customers who make purchases in a modern stores. At least customers have ever purchase in a modern store is considered to have be able to evaluate the services provided in the modern stores.Based on testing using multiple regression dimensions of tangibles, reliability, responsiveness, assurance and empathy simultaneously influence on customer satisfaction on modern stores in Yogyakarta. Partially tangibles no effect on customer satisfaction on modern stores in Yogyakarta. While reliability, responsiveness, assurance and empathy in partial effect on customer satisfaction on modern stores in Yogyakarta.Keywords:Bukti Fisik, Kehandalan, Daya Tanggap, Jaminan, Empati, kepuasan pelanggan.